Peran Ekspresi Gen Heat Shock Protein (HSP70) terhadap Respon Fisiologis Ikan Nila (Oreochromis niloticus) pada Stres Suhu Tinggi - Rina Wulandari; Andi Prakoso (Insight of Biology, 2026)
Elevated water temperature is a major stressor in aquaculture systems that disrupts the physiological stability of Nile tilapia (Oreochromis niloticus). This study aims to analyze the role of heat shock protein 70 (HSP70) gene expression in response to high temperature stress and its association with physiological changes in fish. The study applies a synthesis of empirical data from experimental research that measures molecular, biochemical, and physiological responses to elevated temperature exposure. The results show that increased temperature significantly induces HSP70 gene expression as a protective mechanism against protein denaturation and cellular damage. Elevated HSP70 expression correlates with stress indicators, including increased cortisol levels, enhanced antioxidant enzyme activity, and metabolic imbalance. Under higher stress intensity, this protective response fails to fully compensate for cellular damage, as indicated by reduced physiological performance and increased tissue damage. These findings confirm that HSP70 functions as a sensitive biomarker for detecting thermal stress and plays a critical role in the adaptive mechanisms of fish under environmental change.